Diagnostic value of platelet indices for neonatal bacterial sepsis - Ading Rohadi; Afifa Ramadanti; Indrayady Indrayady; Achirul Bakri (Paediatrica Indonesiana, 2020)
Background Neonatal bacterial sepsis is a major cause of neonatal morbidity and mortality worldwide. Blood culture as a gold standard, as well as C reactive protein (CRP), micro erythrocyte sedimentation rate (micro ESR), white blood count (WBC), and immature-to-total (I/T) ratio as a sepsis screens are currently used methods, but their utility may be limited due to delayed reporting. Platelet indices are one of the parameters which can be helpful in the diagnosis of neonatal bacterial sepsis. Objective To evaluate the use of platelet indices, either alone or in combination, with other laboratory screening parameters to diagnose neonatal bacterial sepsis. Methods Neonates admitted to the Neonatal Unit of RSUP Dr. Muhammad Hoesin Hospital, Palembang, South Sumatera, and showing symptoms of sepsis were included in this study. Subjects underwent testing for blood culture, sepsis screen (CRP, micro ESR, WBC, I/T ratio), and platelet indices [platelet count, mean platelet volume (MPV), and platelet distribution width (PDW)]. Results The 107 neonates who fulfilled the inclusion criteria consisted of 42 neonates with proven bacterial sepsis (positive blood culture), 10 neonates with probable bacterial sepsis (positive sepsis screen and negative blood culture), and 55 with clinical bacterial sepsis (negative in both blood culture and sepsis screen). There were no significant differences in platelet count among the proven bacterial sepsis, probable bacterial sepsis, and clinical bacterial sepsis groups. Platelet count < 150,000/ml, PDW Â³ 16.8 fL, MPV Â³ 10.8 fL and combinations of the three, were highly specific markers for proven sepsis, with specificities of 92.3%, 97%, 75.4%, and 80%, respectively. However, all of these parameters were poor predictive markers for positive cultures in neonatal clinical bacterial sepsis, with sensitivities of 19%, 7.1%, 35.7%, and 23.8%, respectively. Conclusion Platelet indices have high specificity but low sensitivity for the prediction of proven neonatal bacterial sepsis.